Quality-of-life outcomes in transoral robotic surgery - Hurtuk, Agnes M; Marcinow, Anna; Agrawal, Amit; Old, Matthew; Teknos, Theodoros N; Ozer, Enver (Otolaryngology-head and neck surgery, 2012)
To report long-term, health-related quality-of-life (HRQOL) outcomes in patients treated with transoral robotic surgery (TORS). Prospective, longitudinal, clinical study on functional and HRQOL outcomes in TORS. University tertiary care facility. Patients who underwent TORS were asked to complete a Head and Neck Cancer Inventory before treatment and at 3 weeks and 3, 6, and 12 months postoperatively. Demographic, clinicopathological, and follow-up data were collected. Sixty-four patients who underwent TORS were enrolled. A total of 113 TORS procedures were performed. The mean follow-up time was 16.3 ± 7.49 months. The HRQOL was assessed at 3 weeks and at 3, 6, and 12 months, with a response rate of 78%, 44%, 41%, and 28%, respectively. TORS was performed most frequently for squamous cell carcinoma (88%). There was a decrease from baseline in the speech, eating, aesthetic, social, and overall QOL domains immediately after treatment. At the 1-year follow-up, the HRQOL scores in the aesthetic, social, and overall QOL domains were in the high domain. Patients with malignant lesions had significantly lower postoperative HRQOL scores in the speech, eating, social, and overall QOL domains (P < .05). Patients who underwent adjuvant radiation therapy or chemotherapy and radiation therapy had lower postoperative scores in the eating, social, and overall QOL domains (P < .05). The preliminary data show that patients who undergo TORS for malignancies and receive adjuvant therapy tend to have lower HRQOL outcomes. TORS is a promising, minimally invasive, endoscopic alternative surgical treatment of laryngopharyngeal tumors.